The assessment of oral health-related quality of life by factor analysis in patients with Behcet's disease and recurrent aphthous stomatitis - MUMCU, GONCA; DİRESKENELİ, RAFİ HANER; ERGUN, SAFİYE ATLAS TÜLİN (WILEY, 2007)
BACKGROUND: The aim of the study was to test multidimensional properties of oral health impact profile-14 (OHIP-14) in Behcet's disease (BD) and recurrent aphthous stomatitis (RAS) patients with active oral ulcers. METHODS: Ninety-six BD patients, 28 patients with RAS and 117 healthy controls (HC) were included in this study. In patients with active oral ulcers, the frequency and healing time of ulcers were recorded. Multidimensional properties of OHIP-14 were examined by factor analysis. RESULTS: Factor analysis revealed three subscales and explained 66.49% of overall variance in these patients with active oral ulcers. The score of Subscale 1 was positively correlated with the recurrence of oral ulcers per month (P = 0.037). Subscale 3 scores of the patients treated with colchicine were worse than those treated with immunosuppressives (P = 0.035). CONCLUSIONS: The factor structure of OHIP-14 was found to be reliable and sensitive to clinical parameters and treatment modalities in active patients.
Keywords: Behcet's disease; factor analysis; gender; oral ulcers; quality of life; recurrent aphthous stomatitis; treatment modalities; CENTERED OUTCOME MEASURES; IMPACT PROFILE; RADIOTHERAPY; VALIDATION; SEVERITY